Preferensi Lokasi Industri Menengah Di Wilayah Kabupaten Malang - Noor, Raffli; Marsoyo, Agam; Pramono, R. Widodo Dwi (Fakultas Teknik, Universitas Brawijaya, 2018)
Location is one of the important factors for economic activity including industrial activities. Therefore, the determination of industrial site must consider the factors that influence the location. The purpose of this study is to know the spatial distribution pattern of medium industries and to measure the influence of geographical factors (raw materials, human capital, market, transportation, and utility) to medium industries location preference in Malang Regency. The method used in this research is deductive method with quantitative analysis. To know the pattern of spatial distribution of medium industries, this research used Moran's I Index analysis, while to measure the influence of geographical factor to medium industries location preference, it used discriminant statistical analysis. The result of analysis using Moran's I Index states that spatial distribution pattern of medium industries is spread randomly. Factors affecting the preferences of medium-sized industrial sites to be close to the road or far from the road based on discriminant statistical analysis results are; (i) the distance between the source of raw materials and the industrial site; (ii) distance of workforce with industrial site; (iii) distance of industrial site with utility; (iv) market distance with industrial site; and (v) the distance of the industrial site to the owner's home. The most influential factor is the distance of industrial site with the house of the industry’s owner and the distance of industrial site with utility because it has the biggest function coefficient value.Keywords: location preferences, intermediate industries, geographic factors.